The Power of Purpose To Grow and to Give for Life - Leider, Richard J. (Berrett-Koehler Publishers, Incorporated, 2025)
Legendary personal coach Richard Leider, creator of the purpose movement teams, with David Shapiro to bring new stories, new lessons, and an all-new purpose manifesto to a new generation of readers
Description based on publisher supplied metadata and other sources